2015
DOI: 10.1186/s12889-015-2173-8
|View full text |Cite
|
Sign up to set email alerts
|

Availability and acceptability of HIV counselling and testing services. A qualitative study comparing clients’ experiences of accessing HIV testing at public sector primary health care facilities or non-governmental mobile services in Cape Town, South Africa

Abstract: BackgroundThe South African government is striving for universal access to HIV counselling and testing (HCT), a fundamental component of HIV care and prevention. In the Cape Town district, Western Cape Province of South Africa, HCT is provided free of charge at publically funded primary health care (PHC) facilities and through non-governmental organizations (NGOs). This study investigated the availability and accessibility of HCT services; comparing health seeking behaviour and client experiences of HCT across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
4
14
0
1
Order By: Relevance
“…This highlights the close proximity of the HTS to the user. This finding is in agreement with previous studies showing that mobile services are conveniently situated in communities, 14 providing users with the immediate opportunity to test, 13 and that physical proximity of health care is no longer a problem for reaching public facilities. 19 Findings may be different in rural settings, where the service may be further from the user.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This highlights the close proximity of the HTS to the user. This finding is in agreement with previous studies showing that mobile services are conveniently situated in communities, 14 providing users with the immediate opportunity to test, 13 and that physical proximity of health care is no longer a problem for reaching public facilities. 19 Findings may be different in rural settings, where the service may be further from the user.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings nevertheless replicate findings in previous studies: high levels of patient acceptability were reported for mobile HTS, 14 and mobile HTS were found more acceptable than HTS at public facilities in terms of waiting times, cleanliness and perceived friendliness of staff. 13 Our study showed that although user satisfaction at the public facility was high, satisfaction levels were more widely distributed than at mobile and stand-alone modalities.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Fotso et al . and Meehan et al . submitted that it is not only enough to increase the availability of health services, but also make such services available to poor at affordable cost.…”
Section: Discussionmentioning
confidence: 99%
“…Queens, and Staten Island); Fig 1B displays these cases on a map as a percentage of 49 total ZCTA population. 50…”
Section: Introductionmentioning
confidence: 99%